Neutral uranium dimer complexes and selective extraction properties of a new paratertiary butyl 1,3-acid-diethyl amide substituted calix[4]arene ligand - Kan, M; Nicholson, G; Horn, I; Williams, G; Beer, P; Schmitt, P; Hesek, D; Drew, M; Sheen, P (1998)
The solvent extraction of uranium(VI) with a paratertiary butyl 1,3-acid-diethyl amide substituted calix[4]arene ligand in dichloromethane has been studied. UO2+2was found to extract into the dichloromethane phase with a metal:ligand ratio of 1. X-ray crystallographic analysis of a single crystal indicated a dimeric species of 2 UO2+2:2 ligands. The extraction mechanism is pH dependent due to the increased availability of deprotonated hydroxyl groups with increase in pH.